Application of Hydrodynamic Cavitation to Wastewater Treatment - Tao, Yuequn; Cai, Jun; Huai, Xiulan; Liu, Bin; Guo, Zhixiong (Chemical engineering & technology, 2016)
Hydrodynamic cavitation is a promising application in wastewater treatment due to its simple reactor design and capacity in large‐scale operation. Theoretical studies including the basic mechanism of pollutant degradation, modeling of pressure distribution in the cavitation reactor, and bubble dynamics models coupled with chemical reactions are evaluated. Experimental setups with different cavitation reactors and operation parameters are compared for degrading specific kinds of pollutants. The effort directions for both theoretical and experimental investigations are suggested on the basis of the reviewed contents. Easy large‐scale operation, effective combination with intensified strategies, and capability to deal with biorefractory or toxic compounds contribute to the great potential of hydrodynamic cavitation. Theoretical and experimental aspects of hydrodynamic cavitation applied to wastewater treatment are reviewed. Experimental setups, theoretical models, and research results are compared and promising synergetic approaches are described. The future potential of hydrodynamic cavitation in wastewater treatment depends on the design of energy‐efficient and economic reactors.